2020
DOI: 10.3390/ijms21249659
|View full text |Cite
|
Sign up to set email alerts
|

Recontamination of Healthcare Surfaces by Repeated Wiping with Biocide-Loaded Wipes: “One Wipe, One Surface, One Direction, Dispose” as Best Practice in the Clinical Environment

Abstract: The wiping of high-touch healthcare surfaces made of metals, ceramics and plastics to remove bacteria is an accepted tool in combatting the transmission of healthcare-associated infections (HCAIs). In practice, surfaces may be repeatedly wiped using a single wipe, and the potential for recontamination may be affected by various factors. Accordingly, we studied how the surface to be wiped, the type of fibre in the wipe and how the presence of liquid biocide affected the degree of recontamination. Experiments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…At least eight samples were collected from surfaces at each timepoint (Day 1, Day 7, Day 14, and Day 28) after the installation of cleanSURFACES ® . Findings from disinfection literature have reported surface recontamination within minutes to days after decontamination events (9,10). Post-intervention timepoints for the current study were selected based on disinfection literature and previous cleanSURFACES ® studies that demonstrated significant impacts on bioburden after two weeks (13, 20).…”
Section: Site Information Study Design and Sampling Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…At least eight samples were collected from surfaces at each timepoint (Day 1, Day 7, Day 14, and Day 28) after the installation of cleanSURFACES ® . Findings from disinfection literature have reported surface recontamination within minutes to days after decontamination events (9,10). Post-intervention timepoints for the current study were selected based on disinfection literature and previous cleanSURFACES ® studies that demonstrated significant impacts on bioburden after two weeks (13, 20).…”
Section: Site Information Study Design and Sampling Methodologymentioning
confidence: 99%
“…There is a wide variety of hospital practices ranging from chemical-based disinfectants to ultraviolet light, commonly used for environmental safety. Although these methods are effective, they do not provide continuous efficacy, as the literature demonstrates surface re-contaminated occurs within minutes of decontamination (9,10). Re-contamination of indoor surfaces is thought to occur for several reasons, including the fact that building inhabitants, like patients and caregivers, are estimated to constantly shed up to 37 million microbes/hour (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…One known vulnerability for infection control is the perpetual contamination of high-touch surfaces. Surfaces are typically disinfected with chemical-based cleaners, which have limited efficacy beyond the moment of cleaning ( Edwards et al., 2020 ). Thus, surfaces are quickly re-contaminated and serve as reservoirs of pathogens until they are cleaned again ( Scott, 2009 ; Attaway et al., 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, as much as 40% of HAIs are attributable to contamination of environmental surfaces within healthcare facilities ( Weber and Rutala, 2013 ). Because recontamination of surfaces can occur within minutes to days after disinfection events, efforts are underway to develop products to reduce surface contamination even as those surfaces are being used ( Kwan et al., 2018 ; Edwards et al., 2020 ). The present study focuses on a unique approach: evaluating the efficacy of antimicrobial self-cleaning mats for use on select, high-touch surfaces in a LTCF.…”
Section: Introductionmentioning
confidence: 99%
“…The use of disposable disinfectant wipes in the healthcare industry is widespread to aid infection prevention and control practices. Within the healthcare industry, the message "one-wipe, one-surface, one-direction, dispose (of the wipe)" has been recommended since 2009 to prevent the spread of human pathogens across surfaces(Edwards et al, 2020;…”
mentioning
confidence: 99%